Smart traffic light in terms of the Cognitive road traffic management system (CTMS) based on the Internet of Things - Miz, V.; Hahanov, V. I. (EWDTS, 2014)
This work is aimed to describe a cognitive traffic management system (CTMS) based on the Internet of Things approach. Telecommunication technologies, which can be used for the system development and deployment, are analyzed. Smart traffic light integration is proposed as a replacement of the existing traffic lights. The main purpose of such replacement is to optimize traffic management processes which are made by government authorities. Smart traffic light integration excludes mistakes caused by human factor. Proposed approach can be used as a part of e-government system in further. From decade to decade global infrastructure projects are connecting the World – transcontinental railways and highways of the USA, the BAM project of the USSR, the Channel Tunnel beneath the English Channel. These projects became a strong development catalyst for the largest economies of the past and present. Laying underwater transatlantic communication cable and the Internet creation has begun development of the global information infrastructure. The latest achievements in wireless technologies opened new prospects for the Internet services development and popularization. The next constructive step was the Cloud computing technologies and services. Nowadays developers are able to scale computing power and storage capacity depending on their needs due to unlimited scaling opportunity of the Cloud technologies. Increasing mankind needs require the next big step towards information infrastructure development. Fastmoving world needs the infrastructure that allows connecting not only computer devices and systems, but all things which surround people in their everyday life as well. The Internet of Things (IoT) is a new paradigm, which involves intercommunication between different things without human intervention, automated collection, processing and analysis of large amounts of data, generated by the sensors. The IoT makes possible high-accuracy probabilistic behavioral environmental models development. These models allow increasing the levels of everyday life comfort and security due to continuous monitoring of the data obtained from sensors in real time. In the long term IoT will let more effective resource spending owing to Smart cities and e-government concepts implementation optimizing and automating everyday city life management. Smart traffic light, integrated into the IoT as a part of CTMS, makes possible development of a new generation information infrastructure. The main target of this infrastructure is an effective and optimal road traffic management. Big Data applications allow performing high-accuracy probabilistic analysis. Such analysis increases cognitive features of the system and CTMS is getting more and more autonomous and independent. Human's interventions become as less as possible, as a consequence number of errors, caused by human factor, declines as well.
Keywords: Smart traffic light in terms; Cognitive road traffic management system; based on the Internet of Things; CTMS